Serial integration of Dean-structured sample cores with linear inertial focussing for enhanced particle and cell sorting - Holloway, Paul M. (Biomicrofluidics, 2018)
In this contribution, a channel aspect ratio of >2 was used to access high velocity regimes to provide confined sample cores by Dean focussing in advance of linear inertial focussing. This produces a singular separation origin with a mirrored transport path for efficient particle and blood cell sorting, while also increasing the spatial resolution for multiscale sorting.